Emotional Intellegence Dan Organizational Culture Untuk Meningkatkan Internal Service Performance Pada Karyawan Puskesmas Sidoarjo - Anggita Fitrianah Ramadhani; Amiartuti Kusmningtyas (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research aims to determine emotional intelligence and organizational culture to improve the internal service performance of Sidoarjo Health Center employees. There is a population needed in this research, namely 50 employees. In this study, researchers used all community health center employees, both paramedics and non-medical employees, with respondent characteristics based on age, gender, educational background, and length of work. Sampling In this research he author used a saturated sample where all members of the population were used as research samples.So this research uses a questionnaire filled out by respondents and used as data for this research. The analysis technique used is simple linear regression analysis. Hypothesis testing uses (a T-test), while the data analysis methods used include a validity Test and Reliability Test. The results of this research show that Emotional Intelligence and Organizational Culture influence Internal Service Performance. The result obtained t-count of 11.438 is greater than the t-table 2.01063 with a significant value of 0.000 > 0.50, which shows that the results are statistically significant. Furthermore, the emotional intelligence variable has a significant impact on internal service performance, with a t-count of 12.039, greater than the t-table 2.01063 with a significant value of 0.000 > 0.50.